The effects of preoperative video-assisted education on anxiety and comfort after breast cancer surgery: Nonrandomized controlled study - Güzel, Neriman; Yava, Ayla; Koyuncu, Aynur; Yava, Ayla; Koyuncu, Aynur (W.B. Saunders, 2024)
Purpose: This study aimed to determine the effects of video-assisted education given before breast cancer surgery on patients' anxiety and comfort. Design: A nonrandomized, controlled, quasi-experimental model was used. Methods: The study was conducted in the general surgery clinic of a public hospital. Seventy patients voluntarily participated in the study, 35 of them were in the Control (CG) and 35 of them were in the Experimental Group (EG). While routine treatment and care were given to CG, a video-assisted education was also provided to EG. The data were collected using the Personal Information Form, State-Trait Anxiety Inventory (STAI), and General Comfort Questionnaire (GCQ). The patients in both groups filled in the STAI and GCQ on the first day preoperatively, STAI-S and GCS on the second postoperative day and STAI-S on the tenth day after surgery. P < .05 was accepted as a statistical significance value. Findings: The groups were similar in terms of descriptive features and preoperative anxiety scores (P > .05). Postoperative second and tenth-day anxiety scores were significantly higher in CG (43.97 ± 9.42 and 39.45 ± 3.88) compared to EG (33.29 ± 4.94 and 33.31 ± 3.01) (P < .05). In terms of the mean scores of the GCQ and its subscales of comfort, preoperative comfort was found to be lower than postoperative comfort level (P < .05). Conclusions: Preoperative video-assisted education decreased the anxiety level and increased the comfort level in EG. We conclude that the use of video-assisted education in reducing anxiety and increasing the perception of comfort in breast cancer surgery patients would be beneficial. © 2024 The American Society of PeriAnesthesia Nurses
Keywords: anxiety; breast cancer surgery; comfort; nurse; video-assisted education